Proline‐Selective Electrochemiluminescence Detecting a Single Amino Acid Variation Between A1 and A2 β‐Casein Containing Milks - Eunkyoung Kim; Chen‐Yu Chen; Monica J. Chu; Mya F. Hamstra; William E. Bentley; Gregory F. Payne (Advanced Science)
Abstract The proline amino acid and prolyl residues of peptides/proteins confer unique biological and biochemical properties that motivates the development of proline‐selective analysis. The study focuses on one specific class of problem, the detection of single amino acid variants involving proline, and reports a Pro‐selective electrochemiluminescence (ECL) method. To develop this method, the A1‐/A2‐ variants of milk's β‐casein protein are investigated because it is a well‐established example and abundant samples are readily available. Specifically, β‐casein has 209 amino acids with 34 (or 35) proline residues: the A1‐variant has a Pro‐to‐His substitution at position 67 (relative to the A2 variant). The study shows that proline's strong luminescence allows the generic discrimination of: Pro from other amino acids; an A2‐oligopeptide from an A1‐oligopeptide; the A2‐β‐casein variant from the A1‐variant; and commercially‐available A2 milks from A1‐containing regular milks. The evidence indicates that luminescence depends on proline content and accessibility, as well as signal quenching. Compared to conventional immunoassays, the ECL method is simple, rapid, and inexpensive. Further, the ECL‐method is Pro‐selective (vs molecularly‐selective like typical immunoassays) which should make it broadly useful for studying the role of proline in biology and especially useful for tracking the digestion of proline‐rich proteins in the diet.